2015
DOI: 10.1001/jamadermatol.2015.2389
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chromosomal Translocation Associated WithCOL1A2-PDGFBGene Fusion in Dermatofibrosarcoma Protuberans

Abstract: IMPORTANCE Dermatofibrosarcoma protuberans (DFSP) is a rare skin cancer that develops in the deep dermis to subcutaneous adipose tissues. A COL1A1-PDGFB gene fusion, leading to the constitutive expression of PDGFB, is the tumorigenic mechanism in most DFSP cases. OBJECTIVES To evaluate the specificity of PDGFB expression as a diagnostic marker of DFSP and to determine whether other pathomechanisms (ie, gene fusions) exist in patients with DFSP without the COL1A1-PDGFB fusion gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 22 publications
4
37
0
Order By: Relevance
“…Ultimately the COL1A1‐PDGFB fusion gene was cloned, which fairly consistently pairs exon 2 of PDGFB with numerous potential exons of COL1A1 . This fusion product has been identified in 85%‐96% of cases . The incidence appears to increase with the application of more sensitive detection assays; nevertheless, this still implies that a subset of cases may have an alternate fusion gene.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately the COL1A1‐PDGFB fusion gene was cloned, which fairly consistently pairs exon 2 of PDGFB with numerous potential exons of COL1A1 . This fusion product has been identified in 85%‐96% of cases . The incidence appears to increase with the application of more sensitive detection assays; nevertheless, this still implies that a subset of cases may have an alternate fusion gene.…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that in over nine‐tenths DFSP cases, a translocation between chromosomes 17 and 22 [t(17;22)(q22;q13)] can be found, which induces the formation of a fusion gene between COL1A1 and PDGFB genes, leading to the overexpression of platelet‐derived growth factor receptor β (PDGFRB) . It is well‐established that platelet‐derived growth factor (PDGF) signaling pathways play crucial roles in many physiological and pathological processes, such as stimulating the proliferation of multiple cells, stimulating collagen synthesis, and promoting tissue fibrosis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The histological origin and pathogenesis of DFSP are not yet fully understood. Molecular analysis has revealed a translocation between chromosomes 17 and 22 [t(17;22)(q22;q13)] in most DFSP cases, which provides a new adjuvant therapeutic option for this tumor. Yet so far, surgical resection remains the optimal curative treatment for DFSP.…”
Section: Introductionmentioning
confidence: 99%
“…While the reason for this is not known. In addition to CD34, recent studies demonstrated that the analyses of PDGFβ and nestin expression were also effective for pathological diagnosis of DFSP 16, 17. Unfortunately, none of these markers are specific and are not sufficient to distinguish DFSP from other types of cutaneous tumors as alone.…”
Section: Discussionmentioning
confidence: 99%